1990
DOI: 10.1007/bf02578630
|View full text |Cite
|
Sign up to set email alerts
|

Balloon debanding of the pulmonary artery

Abstract: Clinical balloon debanding of the pulmonary artery is reported in two patients, 6 months and 4 years of age. The band was made of Dacron, and was closed with one single polypropylene suture. This suture was subsequently ruptured with a balloon inflated within the pulmonary artery at the site of the band. Balloon debanding relieved the gradient almost completely in the two patients. No problems occurred during the procedure. In the future this may prove to be an efficient and reliable way to remove the effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…3 In 1990, this same group of investigators reported balloon debanding of the MPA in two children at 6 mo and 4 y of age. 4 This patient was urgently transferred to the operating room for surgical band removal. The other two patients had successful debanding with a decrease in the mean pullback gradient across the MPA of 38 and 56%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…3 In 1990, this same group of investigators reported balloon debanding of the MPA in two children at 6 mo and 4 y of age. 4 This patient was urgently transferred to the operating room for surgical band removal. The other two patients had successful debanding with a decrease in the mean pullback gradient across the MPA of 38 and 56%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…However, technical considerations limited the procedure. Difficulties with the manipulation of large balloon catheters (8-Fr) and stiff balloons led the authors to postulate that whereas the procedure is hampered by cumbersome tools, the development of more precise equipment may render the procedure feasible [2]. Currently, with the availability of softer, more responsive and kink-resistant catheters as well as improved more flexible wires and lower-profile more compliant balloons, this technique has become more feasible.…”
Section: Discussionmentioning
confidence: 99%
“…Technical considerations, however, have led authors to hypothesize that although cumbersome tools hinder the procedure, the development of more user-friendly equipment may confer greater practicality to the process [2]. Interventional debanding has not been revisited in recent years, but recent improvements in catheter, wire, and balloon design have made the prospect of interventional PAB loosening more feasible.…”
mentioning
confidence: 99%
“…Some may have VSDs which would be accessible to catheter‐based intervention, but would require surgical intervention only to remove the PA band. The published experience with catheter‐based debanding is very limited, with only a few case reports and some animal studies 8–12 . Neither have any in vitro or in vivo studies been published analyzing the force required or the mechanism by which a PA band can be disrupted.…”
Section: Introductionmentioning
confidence: 99%
“…The published experience with catheter-based debanding is very limited, with only a few case reports and some animal studies. [8][9][10][11][12] Neither have any in vitro or in vivo studies been published analyzing the force required or the mechanism by which a PA band can be disrupted.…”
Section: Introductionmentioning
confidence: 99%